The Development of Concept of Territory in International Relations - Ramadhan, Ghifari Athallah (Global: Jurnal Politik Internasional, 2018)
The concept of territory, a politicized space, is not really explored in International Relations, even though territory is where International Relations happen physically. This article explores the development of the concept of territory in International Relations. By seeing the development of the concept of territory in International Relations, I could see the main arguments regarding territory. For example, I could understand the argument behind the jargon of “borderless world” or “return of geography”. In order to fully explain the development of the concept of territory in International Relations, I divide my research into five parts. First, I would describe the beginning of territory itself; how a neutral geographical space turned into political geographical space. Second, I would talk about the implication of politicization of the geographical space itself, geopolitics. Third, I would describe the critics of the concept of territory and also geopolitics. This will be joined by the fourth part about the respond the critics of the concept of territory and geopolitics. Lastly, I would talk about the non-territorial political community as alternative to traditional territorial-based state. This article then concludes that the definition of territory itself needs to be broadened, as non-spatial space is now a territory, such as the Great Firewall of China. Ultimately, I hope to show the current discussion of territory in international relations study and what could be discussed more in this rarely talked concept in international relations.